FREEDOM OF EXPRESSION AND PROTECTION OF PERSONAL DATA ON THE INTERNET: THE PERSPECTIVE OF INTERNET USERS IN SERBIA - Mitrović, Marta (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2021)
The paper examines the views of Internet users concerning the protection of their rights on the Internet. The web survey, conducted by the snowball sampling, included 783 Internet users who expressed their views regarding the ways the state (Serbia) and private agents (Facebook and Google) relate to the right of freedom of expression and privacy on the Internet. Also, the survey was used to examine the individual responsibility of users when it comes to the use of Internet services. Several hypotheses suggested that Internet users in Serbia do not have confidence in the country and private actors on the issue of protecting their rights. However, users also do not demonstrate a satisfactory level of individual responsibility. The most important findings indicate that: 1) only one-sixth of the respondents consider that the Government of the Republic of Serbia does not violate the privacy of Internet users; 2) almost half of the respondents do not feel free to express their views criticizing the government; 3) almost 90% of users are not satisfied how Facebook protects their privacy, while it is 1% lower in the case of Google; 4) a third of respondents answered positively to the question whether they had read terms of use of the analyzed companies, but half of them did not give a correct answer to the main questions; 5) only 8.9% of respondents who claimed to have read terms of use are aware of the fact that Facebook shares their data with third parties.
Keywords: social networking sites; search engines; freedom of expression; privacy rights; Internet users; Facebook; Google; self-regulation